(untitled) (Ornitología Colombiana, 2021)
Laguna Verde is a lake located at an elevation of 4300 m in the Los Nevados National Park in the Central Andes of Colombia. During a visit in April 2000, a total of 52 dead birds were found along the lake shore, of which 27 were neotropical migratory birds of two species, 3 represented two local species and 22 were bodies of unidentified passerines. During two subsequent visits no more dead birds were found, and water samples were taken for analysis. These analyses revealed very high concentrations of potentially toxic ammonium salts. The neotropical migrants were well above their previously recorded upper altitudinal limits in Colombia.